Effect of span length on the fit of zirconia framework fabricated using CAD/CAM system - Lee, Jeong-Yol (The Korean Academy of Prosthodontics, 2013)
PURPOSE: The purpose of this study was to evaluate the effect of the span length on the fit of zirconia framework fabricated using CAD/CAM system. MATERIALS AND METHODS: Abutments for single, 4-unit and 6-unit fixed partial prostheses were fabricated. Ten zirconia frameworks were fabricated for each group. The marginal and internal gap were presented by means of replica technique and measured by measuring microscope (AXIO®, Carl Zeiss, Rochester, NY) and software (I-solution®, IMT i-solution Inc., Vancouver, BC, Canada). The results were statistically analyzed by multivariate analysis test and Dunnett T3 test for post hoc test (α=.05). RESULTS: There were statistically significant differences at 2, 4, 7, 8 points (mesio-distal section) and b, d, e, f, g (labio-lingual section). In some marginal reference points of 6-unit group (P<.05), the marginal gap were larger than 120 µm. CONCLUSION: Span length of zirconia core may have an influence on marginal and internal fit. Within the limitation of this study, the increase of span length of zirconia framework of 6 or more-unit fixed partial denture may decrease the marginal and internal fit.